Gaya Hidup, Status Gizi dan Status Menarche Remaja Putri - Tina Yuli Fatmawati; Julaecha Julaecha; Nel Efni (Universitas Baiturrahim, 2023)
Menarche is the first menstruation for girls. . Lifestyle changes are believed to be a major factor in the decline in the age of menarche. Changes in lifestyle are due to the progress of civilization followed by changes in humans, ranging from changes in diet to changes in lifestyle. The most common unhealthy lifestyles are consuming fast food and snacks/snacks, rarely exercising and often accessing adult mass media. The purpose of this study was to determine the relationship between lifestyle and the incidence of menarche in students at Junior High School. Design This research is a quantitative study with the Cross Sectional method (cross-sectional) which aims to see the relationship between the dependent variable and the independent variable. This research was conducted at SMP N Jambi City at 2022 with a sample of 75 people taken by purposive sampling. The instrument used is a questionnaire. Data were analyzed by univariate and bivariate analysis with Chi Square test. The results of the study obtained that the most respondents were at the age of 13 years, namely 29 people (38.7%). The education of the majority of respondents is grade 9 by 43 respondents (57.3%). The description of the menarche status of the majority of respondents is not normal by 38 people (49.3%). Overview The majority of respondents' lifestyle is good by 39 people (52.0%). The majority of respondents have a nutritional status of 38 respondents (50.7%). The results of the Chi-Square test obtained p value = 0.116 > (0.05), meaning that there is no relationship between lifestyle and the incidence of menarche in students. Regular education is needed about healthy lifestyles and the participation of parents to form a healthy lifestyle for young women